(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Objectives: The objective of this research is to examine how different physical therapy techniques affect the functional status & pain levels of individuals suffering from non-specific LBP. Methods: Participants in this randomized-controlled study ranged in age from 34 to 62 years and had non-specific persistent LBP for over 12 weeks without neurological damage. The study lasted from February 2021 to August 2022 & comprised 66 females and 38 males. The mean age was 50.3±12.5 years. There was a physical treatment group with 55 patients & control group with 55 patients. Medical care & exercise were provided to both groups; the physical therapy group additionally received physiotherapy methods. Results: 110 patients followed up one year. Treatment resulted in a significant improvement (p<0.5) in the VAS, ODI, & ILBP in both groups when compared to values before treatment. Comparing the physical therapy group & control group, there were notable differences in the VAS, ODI, & ILBP scores at 3 months and 1year post-treatment (p<0.05). Conclusion: Physical therapy is one component of a multidisciplinary strategy that should be used to treat non-specific chronic low back pain in order to improve functional status & pain levels in the long run.